Comparison of Tributyrin and Coated Sodium Butyrate as Sources of Butyric Acid for Improvement of Growth Performance in Ross 308 Broilers - Lum , J.; Sygall, R.; Felip, J.M. Ros (International Journal of Poultry Science, 2018)
Background and Objective: Butyric acid in the form of fat-coated sodium or calcium butyrate has been widely used in commercial poultry production to improve body weight gain and reduce feed conversion. However, a quality coating process reduces the butyrate content and adds additional cost. Tributyrin, a glyceride containing three butyrate molecules attached to a glycerol backbone, is an alternative source of dietary butyrate which does not require a coating and can pass through the upper gastrointestinal tract to release butyric acid in the small intestine after cleavage by pancreatic lipase. The aim of this study was to compare the effects of two sources, coated sodium butyrate and tributyrin, on broiler growth performance. Methodology: In this study, two treatment diets were formulated at an iso-butyric level with either tributyrin or fat-coated sodium butyrate and compared to a control diet for body weight gain and feed conversion ratio over 35 days in Ross 308 broilers. Results: Both treatment diets showed significant improvements in body weight gain during the grower and finisher phases of the trial, with tributyrin having a numerical though not significant advantage over the sodium butyrate group. Feed conversion ratio was also significantly improved in both treatment groups during the grower phase of the trial and for the entire trial. No significant differences were seen between the tributyrin and sodium butyrate groups. Conclusion: The trial suggests that tributyrin is as effective as a fat-coated sodium salt for improvement of broiler performance and may confer advantages over traditional protected butyric acid salts.